Preference of Tribolium confusum (Coleoptera: Tenebrionidae) adults to grain patches under constant and rising temperatures. (January 2021) - Lü, Jianhua; Jian, Fuji; Fields, Paul
Abstract: Heat treatment, an environmental friendly insect control method, has been applied to disinfest grain storage and food processing facilities. Movement of Tribolium confusum adults into grain piles (0.1, 0.5, 1.0, or 5.0 kg oat groats) was investigated at constant temperatures (30, 35, 37.5, 40, 45, or 50 °C) or rising temperatures (at a rate of 0.05 °C/min from 24 to 54 °C in laboratory, or from approximately 30 to 60 °C in a mill during a heat treatment). Adults moved among locations, paper surface, surface of grain pile and inside grain pile. There was preference for the grain at ≤37.5 °C. No single adult always stayed inside grain piles at 30 °C. At rising temperatures, adults preferred grain piles (on the surface of or inside grain piles) and moved into cold grain regardless of adult introduction methods (introduced on surface of groats piles, on paper, or premixed with groats). Rising temperatures did not drive adults out of grain piles during heat treatment. Highlights: Movement of confused flour beetles was studied in an oven and in a mill. At constant temperatures, adults preferred grain piles instead paper surface. No single adult always stayed inside grain piles at 30 °C. At rising temperatures, adults preferred grain piles and moved into cold grain. Rising temperatures did not drive adults out of grain piles.